DAYA PARASITASI Apanteles flavipes Cam. (Hymenoptera: Braconidae) PADA PENGGEREK BATANG TEBU BERGARIS (Chilo sacchariphagus Boj.) (Lepidoptera: Pyralidae) DI LABORATORIUM - Susanti Oktaviana Simanjuntak; Maryani Cyccu Tobing2 Maryani Cyccu Tobing2 Maryani Cyccu Tobing2; Darma Bakti2 Darma Bakti2 (Universitas Sumatera Utara, 2013)
The Ability of Parasitoid Apanteles flavipes Cam. (Hymenoptera: Braconidae) on Sugarcane Stem Borer (Chilo sacchariphagus Boj.) (Lepidoptera: Pyralidae) in the Laboratory, The sugarcane stem borer Chilo sacchariphagus Boj. (Lepidoptera: Pyralidae) is one of pest that attack sugarcane crop in North Sumatera. The objectives of this research were to study the ability of parasitoid Apanteles flavipes Cam. (Hymenoptera: Braconidae) to control C. sacchariphagus. The research was conducted at the Laboratory of Sugarcane Research and Development Sei Semayang, Binjai, Medan, North Sumatera from Mei to July 2012. This method used Randomized Complete Design Factorial with two factors. The first factor was age of A. flavipes (control, 0, 1, 2, 3, 4 days) and the second factor was number of C. sacchariphagus (1, 3, 5, 7 larvae) with three replications. The results showed that the percentage of parasitation depend on age of A. flavipes and number of C. sacchariphagus. The result showed that the highest percentage of parasitation (48.02%) on 0 day A. flavipes and the lowest (11,11%) on 4 days A. flavipes. The highest percentage of parasitation (61,11%) in number of host was 1 larvae C. sacchariphagus and the lowest (9,53%) in 7 larvae C. sacchariphagus. Sex ratio of male and female was 1: 1.99. Keywords : Parasitoid, Apanteles flavipes, percentage parasitation, sex ratio, Chilo sacchariphagus.